Portrayal of gender roles in Emirati television dramas: a content analysis - Gjylbegaj, Viola; Radwan, Ahmed Farouk (Frontiers in Sociology, 2025)
This research investigates the portrayal of gender roles in Emirati television dramas and movies, contextualizing them within the evolving socio-cultural landscape of the United Arab Emirates (UAE). The study conducts a comprehensive analysis of Emirati dramas and movies, categorizing prevalent gender role trends and their alignment with Emirati culture. Through content analysis, the research identifies four primary patterns: the ratio of male to female characters, gender role diversity and plot-power, themes relating to culture and religion, and the intensity of gender role manifestation with external factors. Findings reveal a predominant focus on male characters in Emirati media, reflecting traditional values where men are depicted as providers and leaders, while women are often relegated to caretaking roles. Implications of the research highlight a gradual shift toward gender equality in the UAE, evidenced by the increasing participation of women in the workforce. However, entrenched cultural values continue to influence societal expectations, perpetuating certain gender stereotypes. The study underscores the importance of media literacy in fostering critical analysis and demands for more nuanced female representation in Emirati media. Recommendations are proposed for media producers and regulators, to collaborate in promoting gender-sensitive content and fostering social change. By embracing evolving gender dynamics while preserving cultural heritage, the UAE has the potential to emerge as a global exemplar of contemporary society, championing diversity and inclusivity on a regional and international scale.